IMPLEMENTASI KEBIJAKAN PENGEMBANGAN PARIWISATA BERBASIS KOMUNITAS - Rahmania Alkadrie E.21110104 (FISIP Universitas Tanjungpura, 2013)
Writing this article is intended to provide an understanding of the implementation of community -based tourism development policy at the Department of Tourism Kabudayaan and Pontianak . Issues concerning the implementation of development programs in the Regional tourism attractions such Pontianak , the attraction potential seen yet developed ( managed ) or has not received the attention of the Regional Government of Pontianak , there are several historical attractions in the city of Pontianak and the dominant of the affairs of the Department of of them are like the Equator Monument , Kadariah palace and tomb of Pontianak Sultanate . Regarding the potential of existing attractions and have not developed or managed optimally . The results showed that the implementation of the communication in order to develop tourism Equator Monument in Pontianak has not run yet in terms of maximum effective implementation of two-way communication in disseminating these policies are carried out in Disbudpar . Disposition or attitude of local government implementers through Disbudpar Pontianak Pontianak not fully evaluate the condition of existing objects in determining the action to be taken , by improving facilities and infrastructure damaged in the object in question . Then the available resources in order to develop tourism as the Equator Monument Kapuas River is the lack of personnel educational background in tourism , infrastructure and facilities available is not adequate , still minimal ( not optimal ) is movable or immovable . Therefore , the need for exchange of information on the field of tourism , the presence of a good working relationship , the availability of accurate data on the profile of existing attractions in Pontianak , the commitment made ??in the context of tourism promotion stickers, brochures and advertisements about tourism potential .Keywords : Implementation of Tourism Policy, Tourism Development and Tourism, Community Based